2020
DOI: 10.1016/j.matt.2020.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Inch-Size 0D-Structured Lead-Free Perovskite Single Crystals for Highly Sensitive Stable X-Ray Imaging

Abstract: Inch-sized (26 3 26 3 8 mm 3 ), 0D-structured, lead-free, halide perovskite (CH 3 NH 3 ) 3 Bi 2 I 9 single crystals are grown for a high-performance X-ray detector. The X-ray detector shows high sensitivity of 1,947 mC Gy air À1 cm À2 , low detection limit of 83 nGy air s À1 , and short response time of 23.3 ms. The combination of large crystal size and excellent X-ray response allows us to design and fabricate the first 0D-structured lead-free perovskite X-ray imaging system with high resolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
321
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 273 publications
(330 citation statements)
references
References 50 publications
6
321
2
1
Order By: Relevance
“…Once the X-ray was off, the current was interestingly dropped to a value below its baseline and followed by sharp increase. 68 This distinctly different Xray response behaviors were closely associated with the ion migrations in the perovskite, and similar phenomena have been reported elsewhere. 31 As a result of the suppressed ion migration, the 0D perovskite detector exhibited dramatically stabilized baseline ( Figure 5F) and stable photocurrent output under continuous X-ray exposure for 42 hours (Total dose: 2.98 Gy air ).…”
Section: Low-dimension Bismuth Based Halide Perovskitessupporting
confidence: 83%
See 2 more Smart Citations
“…Once the X-ray was off, the current was interestingly dropped to a value below its baseline and followed by sharp increase. 68 This distinctly different Xray response behaviors were closely associated with the ion migrations in the perovskite, and similar phenomena have been reported elsewhere. 31 As a result of the suppressed ion migration, the 0D perovskite detector exhibited dramatically stabilized baseline ( Figure 5F) and stable photocurrent output under continuous X-ray exposure for 42 hours (Total dose: 2.98 Gy air ).…”
Section: Low-dimension Bismuth Based Halide Perovskitessupporting
confidence: 83%
“…The relatively large response time is due to the large carrier transit lengths (thick perovskite), severe ionic migration or long lifetime of trapped carriers. 37,68 Recently, Nie et al demonstrated a remarkably fast response speed (t r :<500 ns, t f : 20 μs) by using a thin (470 nm) 2D perovskite with suppressed ion migration and a photovoltaic device with a large built-in-potential. However, the absorption and the photo-generated current are sacrificed at the same time, as the thin perovskite leads to extremely low absorption (<3%) even for soft X-ray (10.96 keV).…”
Section: Response Speedmentioning
confidence: 99%
See 1 more Smart Citation
“…The p-i-n detectors (ITO/PTAA/(PbI 3 )/C 60 /gold) demonstrated a 10-40-fold higher X-ray absorption coefficient as compared to a Si detector. The existence of the internal field (generated by the different work www.advancedsciencenews.com www.advancedscience.com [ 120] functions electrodes employed), helped to sweep the X-ray generated carriers to the respective electrodes, allowing the demonstration of self-powered X-ray detectors, which is ideal for the detection of low energy X-ray photons. Due to the low dark current, four orders of magnitude higher signals than the dark current at zero bias were recorded -a much higher value than reference Si detectors that showed two orders of magnitude higher SNR.…”
Section: Low-dimensional Perovskitesmentioning
confidence: 99%
“…The second approach that complements the first is to reduce the dimensionality of the perovskite (Figure 1), where the ionmigration is found to be significantly lower, depending on the quality of the layers employed. [119] Liu et al [120] adopted both of these approaches and demonstrated solution-processed, 0D, Pb-free, high-quality MA 3 Bi 2 I 9 single perovskite crystal of inch size for the first time. The perovskite crystals combined all features required for application in direct X-ray detectors, including suppressed ion-migration.…”
Section: Low-dimensional Perovskitesmentioning
confidence: 99%